ANALISIS PENGARUH INDIVIDUALISME - KOLEKTIVISME TERHADAP GAYA MANAJEMEN KONFLIK DI TINGKAT INDIVIDUAL (Studi Eksplorasi Para Manajer di Kota Semarang) - Khadijah, Intan; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2016)
This research has purpose to analyze the influence of individualism - collectivism on conflict management style at the individual level (exploratory study of managers in semarang city).The respondent for this research totaled 80 managers of various companies in Semarang city. Technique of sample collection used Purposive Sampling and used a technique double regression analysis , the analysis includes: test the validity of , a test of reliability , test the assumption of the classics , linear regression test doublet test.Research result showed that collectivism has a negative and significant influence on the conflict management style competing, collectivism has a negative and significant influence on the conflict management style avoiding, collectivism has a negative and significant influence on the conflict management style collaborating, collectivism has a negative and significant influence on the conflict management style accomodating, collectivism has a negative and significant influence on the conflict management style compromising.